Penerapan Nilai-Nilai Agama dalam Mengurangi Pengaruh Game Online di Era Digital (Studi Kasus di SMP Negeri 1 Kopang Lombok Tengah) - Umami, Satria (ANWARUL, 2022)
The purpose of this study is to find out how the role of parents in assisting children in reducing the influence of online games with the application of religious values and to determine the supporting and inhibiting factors in the digital era. In this study the data obtained in the field using observation, documentation and interview techniques. The research method used in this study is qualitative research with a case study approach with two methods of collecting data, namely primary data and secondary data, primary data by interviews and secondary data by collecting from journals, books and archives related to the research objectives. The results of the research on the role of parents in assisting children in reducing the influence of online games with the application of religious values in the digital era.Shows that parents are the main responsibility for inculcating religious values in the digital era and play an active role in reducing their children playing online games for the future of their children's education. In the current digital era, parents play a very important role in instilling religious values and motivating children so that they are not influenced by online games, making the child overwhelmed, confused in interacting with other people and can also damage the morale of the child to be selfish.